2022
DOI: 10.3390/ph15050512
|View full text |Cite
|
Sign up to set email alerts
|

Using a Caenorhabditis elegans Parkinson’s Disease Model to Assess Disease Progression and Therapy Efficiency

Abstract: Despite Parkinson’s Disease (PD) being the second most common neurodegenerative disease, treatment options are limited. Consequently, there is an urgent need to identify and screen new therapeutic compounds that slow or reverse the pathology of PD. Unfortunately, few new therapeutics are being produced, partly due to the low throughput and/or poor predictability of the currently used model organisms and in vivo screening methods. Our objective was to develop a simple and affordable platform for drug screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 123 publications
(151 reference statements)
1
9
0
Order By: Relevance
“…27 ). Our results corroborate well with the published data as some of these molecules demonstrate noticeable rescue effect at one mM concentration 64 66 . Under matched conditions, in the presence of NS132 (50 µM), the total number of intact DA neurons on day 15 was 51, which confirms that NS132 also effectively rescues the degeneration of DA neurons in UA196 worms (Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…27 ). Our results corroborate well with the published data as some of these molecules demonstrate noticeable rescue effect at one mM concentration 64 66 . Under matched conditions, in the presence of NS132 (50 µM), the total number of intact DA neurons on day 15 was 51, which confirms that NS132 also effectively rescues the degeneration of DA neurons in UA196 worms (Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…We also compared the antagonist activity of NS163 and NS132 with various reported ligands using ThT aggregation assay. We used multiple reported ligand inhibitors of αS aggregation, which were commercially available, including Bexarotene 64 , Tyrosol 65 , Valporic acid 66 , and EGCG 67 . The ligands were screened against 100 µM αS aggregation (for four days) at an equimolar ratio using ThT aggregation assay.…”
Section: Resultsmentioning
confidence: 99%
“…These small organisms have mainly been used to acquire knowledge about embryonic development. For example, the zebrafish ( Danio rerio ) has been applied to study the genetic effects of human diseases and drug screening. The fruit fly ( Drosophila melanogaster ) was extensively used to study genetic mutations, heredity, as well as biological processes, including embryonic development, learning, behavior, and aging. Finally, the nematode Caenorhabditis elegans has been used as a model for research in molecular biology, medicine, pharmacology, and toxicology. …”
Section: Microfluidic Devicesmentioning
confidence: 99%
“…Expression of the human PD related protein in nematodes shows age-dependent aggregation, and when expressed in dopaminergic neurones results in neurodegeneration 99 , 100 . It is important to note that those C. elegans expressing α-synuclein have a normal lifespan 101 , 102 but are more sensitive to toxin exposure and dopamine neurone degeneration 102 . The transparency of the nematode enables easy visualization of fluorescent reporters, such that tagging the α-synuclein to GFP or YFP has shown that the resulting aggregates resemble the Lewy body-like inclusions in human PD and lead to increasing toxicity with age 94 , 101 , but has also enabled the identification of neuroprotective genes 94 , 103 and compounds that affect α-synuclein aggregation 101 , 104 .…”
Section: Animal Studiesmentioning
confidence: 99%